Impact of concomitant aortic valve replacement in patients with mild-to-moderate aortic valve regurgitation undergoing left ventricular assist device implantation: EUROMACS analysis - Gliozzi, Gregorio; Nersesian, Gaik; Gallone, Guglielmo; Schoenrath, Felix; Netuka, Ivan; Zimpfer, Daniel; de By, Theo M M H; Faerber, Gloria; Spitaleri, Antonio; Vendramin, Igor; Gummert, Jan; Falk, Volkmar; et al. (Artificial organs, 2025)
INTRODUCTION: Left ventricular assist device (LVAD) therapy may lead to an aortic regurgitation, limiting left ventricular unloading and causing adverse events. Whether concomitant aortic valve replacement may improve outcomes in patients with preoperative mild-to-moderate aortic regurgitation remains unclear. METHODS: A retrospective propensity score-matched analysis of adult patients with preoperative mild-to-moderate aortic regurgitation undergoing durable LVAD implantation between 01/01/2011 and 30/11/2021 was performed. Patients undergoing concomitant valve surgery other than biological aortic valve replacement were excluded, resulting in 77 with concomitant biological aortic valve replacement and 385 without. RESULTS: Following 1:1 propensity score matching, two groups of 55 patients with and without biological aortic valve replacement were obtained, (mean age 59 ± 11 years, 92% male, 59.1% HeartWare). Aortic regurgitation was mild in 72.7% and 76.4% and moderate in 27.3% and 23.6% in non-replacement and replacement cohorts respectively. The 30-day survival was 89.1% vs. 85.5% (p = 0.59), 1-year survival 69.1% vs. 56.4% (p = 0.19), and 2-year survival 61.8% vs. 47.3% (p = 0.10) in the non-replacement and replacement groups, respectively. After a mean follow-up of 1.2 years, non-replacement patients had a higher incidence of pump thrombosis (11 [20%] vs. 3 [5.5%], p = 0.022) and fewer major bleedings (2 [3.6%] vs. 11 [20%], p = 0.008). CONCLUSION: Compared with those treated conservatively, patients with mild-to-moderate aortic regurgitation undergoing concomitant aortic valve replacement during LVAD implantation have a similar survival up to 2 years on support. Patients with concomitant valve replacement had a higher risk of bleeding complications but fewer pump thromboses.
Keywords: výsledek terapie; Heart-Assist Devices; Aortic Valve Insufficiency; LVAD; Male; retrospektivní studie; srdeční selhání; EUROMACS; advanced heart failure; Heart Valve Prosthesis Implantation; Aged; mužské pohlaví; senioři; aortální chlopeň; chirurgická náhrada chlopně; aortální insuficience; Propensity Score; tendenční skóre; Treatment Outcome; Aortic Valve; aortic regurgitation; lidé; ženské pohlaví; Humans; Heart Failure; podpůrné srdeční systémy; Retrospective Studies; Female; lidé středního věku; Middle Aged